Feeding methods for children with cleft lip and/or palate: a systematic review - Duarte,Giesse Albeche (2016)
ABSTRACT INTRODUCTION: Feeding difficulties in children with cleft lip and palate (CLP) are frequent and appear at birth due to impairment of sucking and swallowing functions. The use of appropriate feeding methods for the different types of cleft and the period of the child's life is of utmost importance for their full development. OBJECTIVE: Review studies comparing feeding methods for children with CLP, pre- and postoperatively. METHODS: The search covered the period between January 1990 and August 2015 in the PubMed, LILACS, SciELO, and Google Scholar databases using the terms: cleft lip or cleft palate and feeding methods or breastfeeding or swallowing disorders and their synonyms. This systematic review was recorded in PROSPERO under number CRD42014015011. Publications that compared feeding methods and published in Portuguese, English, and Spanish were included in the review. Studies with associated syndromes, orthopedic methods, or comparing surgical techniques were not included. RESULTS: The three reviewed studies on the period prior to surgical repair showed better feeding performance with three different methods: squeezable bottle, syringe, and paladai bottle. Only one study addressed the postoperative period of cleft lip and/or palate repair, with positive results for the feeding method with suction. Likewise, the post-lip repair studies showed better results with suction methods. After palatoplasty, two studies showed better performance with alternative feeding routes, one study with suction method, and one study that compared methods with no suction showed better results with spoon. CONCLUSION: The studies show that prior to surgical repair, the use of alternative methods can be beneficial. In the postoperative period following lip repair, methods with suction are more beneficial. However, in the postoperative period of palatoplasty, there are divergences of opinion regarding the most appropriate feeding methods.